On the exchange rates behavior by PPP: a test on Malaysian ringgit and US dollar - Pourkalbassi, Farhad; Bahiraie, Alireza; Hamzah, Aishah; Lee, Chin (Academic Journals, 2011)
Exchange rates are important to innumerable economic activities and the exchange rate behavior has long been at the top of the list of research agenda in international finance. This article is another test of the Relative Purchasing Power Parity (RPPP) to explain exchange rate behavior in short terms. The study examine the relative form of Purchasing Power Parity theory with recent monthly exchange rate data of US Dollar and Malaysian Ringgit starting from year 2005, which was the time Malaysia's currency went back to floating system after a few years pegging to US dollar since 1997 Asian Financial Crisis (AFC). Within this study, correlation and Ordinary Least Square (OLS) methods were applied to test the proposed RPPP model. Both the statistical and the observational results show significance power of Relative PPP on explaining exchange rate behavior of the chosen currencies.